The City’s New Suit. Commercial Expansion and Urban Modernization of Bahia Blanca in Panorama (Argentina, 1950-1960) - López Pascual, Juliana (Revista de Historia Social y de las Mentalidades, 2023)
During the central decades of the 20th century, the city of Bahía Blanca (Buenos Aires) underwent fundamental changes in its economic profile, which generated the expansion and consolidation of social sectors linked to commercial, financial and service activities. The material correlate of this process had as one of its manifestations the transformation of the urban physiognomy, in whose central space skyscrapers, galleries and new commercial environments proliferated. This article explores and reconstructs this historical process based on the analysis of the magazine Panorama seeking to account for the representations made by said publication and its visual intervention in the debates around the regional role of the city.